Experimental Investigation of Mechanical Behavior of Bauhinia Racemosa - Based Glass Fiber Reinforced Composite. (2019) - Saravanan, G.; Bhaskar, G.B.; Kaviyarasan, E.; Naveen, B.; Prabakaran, S.; Rajesh, S.
Abstract: The composite materials have high strain energy, high strength to weight ratio compared with other materials. Presently natural composites are widely used in mechanical field. The present work deals with combination of composite material such as Bauhinia racemosa (BR Fiber), Glass fibers reinforced plastics (GFRP) with epoxy resin and hardener. Two specimens such as Specimen 1 and 2 are fabricated with hand layup method with mixing of BR and GFRP composite material as per the ASTM standard the various mechanical properties which include tensile, flexural and impact test are evaluated and compared. The result shows that specimen 2 gives better tensile strength of 28.64 Mpa with more Impact energy of 0.406 kg-m with compared specimen 1. In specimen 1 the flexural strength of 0.14 KN gives good result than specimen 2.